НОРМАТИВНО-ПРАВОВЕ ПІДҐРУНТЯ ОЦІНЮВАННЯ РЕЗУЛЬТАТІВ РОЗБУДОВИ ТЕРИТОРІЙ ВІДНОВЛЕННЯ У ВОЄННИЙ ЧАС: АСПЕКТИ ІДЕНТИФІКАЦІЇ - Rohozian, Yuliia (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2024)
The research article demonstrates the interim study results of theoretical and methodical aspects for assessing the results of the recovery areas development in wartime. The catastrophic consequences of the armed conflict since February 2022 have led to significant changes not only in the military, social, economic, and environmental spheres, but also at the political level, in particular, they have updated the state regional policy. The martial law regime brought changes to the introduction of a new functional typification of territories, distinguishing between recovery areas, areas with special conditions for development, poles of economic growth, and areas of sustainable development. Among these types, it is the territories of recovery that play a key role today, as the recovery of the local and national economy depends on their development. In order to understand the trends in the recovery of these territories, it is necessary to assess their key social and economic indicators during the war, the results of which will give an idea of the pace of development of the main spheres of the territorial community's life. Since the territories of recovery include the territorial communities that have suffered the greatest damage and meet the criteria set out in the current regulatory framework, the following should be considered, these findings are based on an analysis of the current regulatory and legal acts of Ukraine on the restoration and development of regions and territorial communities on the example of Eastern regions. The article reveals the key changes in the state regional policy, identifies 23 communities in Donetsk region and 53 in Kharkiv region that meet the criteria for martial law recovery areas. The clustering of the identified territories made it possible to identify 5 groups of communities with the highest chances of obtaining the status "territories of recovery", as well as to single out 23 territorial communities of Donetsk region and 3 of Kharkiv region that do not meet the criteria at all, and therefore cannot be classified as recovery areas due to the continuation of active hostilities and temporary occupation. The author emphasises the expediency of conducting a scientific socio-economic assessment of the development of these territories and developing practical proposals for their functioning in the wartime and post-war period.